DEVELOPMENT OF PROJECT-BASED LEARNING MODULES ON THE APPLICATION OF PANCASILA PRINCIPLES FOR FOURTH GRADE STUDENTS - febby yunita sari; Zaka Hadikusuma Ramadan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to produce a Project-Based Learning (PJBL) module on the application of Pancasila principles for fourth-grade students. This research is a development study using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This study consists of three stages: Analysis, Design, and Development. The data collection instruments used were questionnaires given to subject matter experts, language experts, and design experts with the appropriate qualifications. The subjects in this study were six expert validators consisting of two subject matter experts, two language experts, and two design experts. The data collection techniques used were interviews using interview sheets and questionnaires using questionnaires validated by subject matter experts, language experts, and design experts. The data analysis technique used in this study was qualitative analysis of comments and suggestions, while quantitative analysis was obtained from validity scores and responses from teachers and students. The validity of the Project-Based Learning (PJBL) module on the Application of the Pancasila Principles has reached a very valid level. The details of the assessment are as follows: the material validation results obtained a percentage of 91.50% in the highly valid category, language experts obtained a percentage of 90.67% in the highly valid category, and design experts obtained a percentage of 88.75% in the highly valid category.